1965
DOI: 10.1083/jcb.27.1.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Differential Response of Sarcoplasm and Myoplasm to Denervation in Frog Muscle

Abstract: Electron microscopic evidence is presented that the early response to denervation ("simple atrophy") of the semitendinosus m. of the frog is characterized by a greater prominence of the sarcoplasmic reticulum and by the presence, in the interfibrillar spaces, of mitochondria which are more numerous and smaller than in normal muscle. In contrast with the dynamic changes of the sarcoplasmic structural components, the myofibrils showed a progressive decrease in diameter after denervation and throughout the period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

1968
1968
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(41 citation statements)
references
References 37 publications
(39 reference statements)
3
37
0
1
Order By: Relevance
“…In accordance with these previous studies, we found disruption of myofibrils, with preserved areas adjacent to disintegrated sarcomers [15,30,31,33] and increased amounts of lipid vacuoles, glycogen granules, and connective tissue [14,15,31,33]. As in the denervation studies, we observed changes in triads and sarcoplasmic reticulum [33,35]. Concerning mitochondria, we did not observe swelling or alterations in cristae and matrix [14,15,32] but only smaller rounded mitochondria, which were irregularly located near the Z-bands.…”
Section: Discussionsupporting
confidence: 77%
“…In accordance with these previous studies, we found disruption of myofibrils, with preserved areas adjacent to disintegrated sarcomers [15,30,31,33] and increased amounts of lipid vacuoles, glycogen granules, and connective tissue [14,15,31,33]. As in the denervation studies, we observed changes in triads and sarcoplasmic reticulum [33,35]. Concerning mitochondria, we did not observe swelling or alterations in cristae and matrix [14,15,32] but only smaller rounded mitochondria, which were irregularly located near the Z-bands.…”
Section: Discussionsupporting
confidence: 77%
“…1973;Go ldspink, 1976) and dystrophic muscles (Williams & Goldspink, 1976) as well as normal innervated ones, are known to grow and add on new sarcomeres in series when held in a lengthened state. These findings suggest that although denervated, or dystrophic, muscles undergo atrophy mainly by decreases in fibre diameters (Muscatello, Margreth & Aloisi, 1965;Rowe & Goldspink, 1969) longitudinal growth can be induced in such muscles by stretching. In the absence of the stretch reflex denervated muscle appears to grow ) and add on new sarcomeres (Goldspink, Tabary, Tabary, Tardieu & Tardieu, 1974) under the influence of passive stretch.…”
Section: F Goldspink Protein T Urnover Of Immobilized M Uscle 27 mentioning
confidence: 96%
“…Although temperature and the low degree of activity may have inhibited the breakdown of proteins, some atrophy was expected at least after more than 3 months of culture at negative strain. In vivo, dry weight of denervated frog muscle was shown to be reduced by 20% within 2 months (Muscatello et al, 1965). Therefore, it can be excluded that the lack of atrophy is due to the culture temperature of 20°C.…”
Section: Fibre Morphologymentioning
confidence: 99%